Cytotoxic and Antimigration Activity of Etlingera alba (A.D.) Poulsen Rhizome. (28th December 2021) - Wahyuni, W.; Diantini, Ajeng; Ghozali, Mohammad; Subarnas, Anas; Julaeha, Euis; Amalia, Riezki; Sahidin, I.
Abstract : Etlingera alba is one of the Etlingera plants that might have anticancer activity. This study aims to investigate the cytotoxic and antimetastatic activity of E. alba rhizome fractions and migration cell assay against MDA-MB-231 cell lines, which are used for triple-negative breast cancer (TNBC) treatment assay. The cytotoxic activity was assayed using CCK-8 assay, while the antimetastatic was assayed using migration cell assay for the fractions A–F. They were followed by LCMS/MS profiling to determine the chemical contents in the most active fraction. According to results obtained, fraction B was the most active fraction for cytotoxic activity with an IC50 value of 65.43  μ g/mL, while fraction E was the most active fraction for antimetastasis activity against migration rate doses of 50, 100, and 200 ppm which were 6.80, 3.66, and 3.00%, respectively. Several compounds in fraction B, such as rengyolone, licochalcone A, sugiol, and spinasterol, might have been known to have activity against cancer cells, as well as aschantin and lirioresinol B dimethyl ether from fraction E. In conclusion, the chemical components from E. alba rhizome fractions provided potency for discovering new agents for cancer treatment, specifically for TNBC.